2007
DOI: 10.1103/physreva.76.013822
|View full text |Cite
|
Sign up to set email alerts
|

Formation of optimal-order necklace modes in one-dimensional random photonic superlattices

Abstract: We study the appearance of resonantly coupled optical modes, optical necklaces, in Anderson localized one-dimensional random superlattices through numerical calculations of the accumulated phase. The evolution of the optimal necklace order m * shows a gradual shift towards higher orders with increasing the sample size. We derive an empirical formula that predicts m * and discuss the situation when in a sample length L the number of degenerate in energy resonances exceeds the optimal one. We show how the extra … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Such a periodic on average model is an optical counterpart of the Anderson model of electronic systems and is widely used for localization studies 12,14,15,19,25 . The transmission coefficients of optical waves are calculated by standard transfer matrix method 25 .…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a periodic on average model is an optical counterpart of the Anderson model of electronic systems and is widely used for localization studies 12,14,15,19,25 . The transmission coefficients of optical waves are calculated by standard transfer matrix method 25 .…”
Section: The Modelmentioning
confidence: 99%
“…Even though NSs can contribute very large transmission, their formation has rigorous conditions, i.e., the nearly-degenerated localized states are required to be evenly distributed inside the system 7,14,16,17 . In general the localized states with similar frequency are not such well distributed in a specific random configuration.…”
Section: Introductionmentioning
confidence: 99%
“…[11]). As mentioned in the beginning, we observe an even more increased α/β ratio, which is 3.4 now.…”
Section: Numerical Resultsmentioning
confidence: 93%
“…Such a reduction then should result in the formation of optimal-order necklaces [7]. The question of how optimal-order necklaces form in 1D random dielectric stack of resonant layers was addressed very recently [11]. Numerical studies showed that the optimal necklace order m tends to shift gradually towards higher orders with increasing the sample size.…”
Section: Introductionmentioning
confidence: 97%
“…This reduction then should result in the formation of optimal-order necklaces [7]. Very recently, the question of how optimal-order necklaces form in 1D random dielectric stacks of resonant layers was addressed [11]. It was shown through numerical studies that the optimal necklace order m shifts gradually towards higher orders with increasing the sample size.…”
mentioning
confidence: 99%